Practices and trends of telework in the Portuguese industry: the results of surveys in the textile, metal and software sectors - Urze, Paula (2008)
The aim of the TeleRisk Project on labour relations and professional risks within the context of teleworking in Portugal – supported by IDICT – Institute for Development and Inspection of Working Conditions (Ministry of Labour), is to study the practices and forms of teleworking in the manufacturing sectors in Portugal. The project chose also the software industry as a reference sector, even though it does not intend to exclude from the study any other sector of activity or the so-called “hybrid” forms of work. However, the latter must have some of the characteristics of telework. The project thus takes into account the so-called “traditional” sectors of activity, namely textile and machinery and metal engineering (machinery and equipment), not usually associated to this type of work. However, telework could include, in the so-called “traditional” sectors, other variations that are not found in technologically based sectors. One of the evaluation methods for the dynamics associated to telework consisted in carrying out surveys by means of questionnaires, aimed at employers in the sectors analysed. This paper presents some of the results of those surveys. It is important to mention that, being a preliminary analysis, it means that it does not pretend to have exhausted all the issues in the survey, but has meant that it shows the bigger tendencies, in terms of teleworking practices, of the Portuguese industry.